Diagnosis of ventricular arrhythmias in patients with post COVID-19 syndrome - Aponte-Hidalgo , Baltazar (2022)
Objective. To identify ventricular arrhythmias in patients suffering from this disease (post VOCID-19 syndrome). Materials and methods. Descriptive, prospective and cross-sectional study. The sample corresponded to 79 patients infected by VOCID-19 diagnosed, treated and discharged from a Venezuelan institution. The most important study variables were: severity by VOCID-19 and types of ventricular arrhythmias. A data collection instrument validated by expert judgement was used. Rhythm Holter was used for cardiovascular evaluation. Descriptive statistics and graphs-figures were used. Results. 45.57% of the patients were female and 54.43% male, the average age was 56 years, with predomium of the age group between 41 and 60 years (49.4%). According to the symptomatology, 31.65% of the patients had a mild disease, 59.5% moderate and 8.86% severe. The most frequent types of arrhythmias according to the type of VOCID-19 suffered were: sinus rhythm (28%) in mild cases; sinus tachycardias (26%) and inappropriate (26%) for moderate cases and ventricular tachycardia (43%) in severe cases. As for the clinical evolution of the patient, in the process of mild disease the evolution was satisfactory of 100%; in the moderate the evolution was 88.5%, and in the severe 16.6%. Conclusion. Holter was able to determine the type of arrhythmia suffered by patients, which was different according to the degree of severity of the disease, so this information could be considered as a predictive factor.